PERSEPSI GURU PAMONG TERHADAP KETERAMPILAN DASAR MENGAJAR MAHASISWA PPL-2 PPKn FKIP UNTAN ANGKATAN 2016 - Wahyu Hermandi; Bambang Budi Utomo; Tomy Sastra Atmaja (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to find the perceptions of tutor teachers on the primary skills of civic education teaching on the teacher students of Civic Education FKIP UNTAN, Batch 2016 in Academic Year 2019/2020 in the teaching practice program (PPL 2). This study is qualitative research using the descriptive method. The participating schools in this study comprise SMAN 3 Pontianak, SMAN 8 Pontianak, SMA Islam Bawari, SMA ISLAMYAH Pontianak, and SMA Muhammadiyah 1 Pontianak. Data sources consist of primary data that includes tutor teachers of the teaching practice program (PPL-2) and secondary data that consists of students who took part as the pupils for the PPL-2 teacher. Data were collected through interviews and documentation studies, using data collection tools in the form of structured interview guides, field notes, and cameras. Data were analyzed through data reduction techniques and data display and confirmed through extended observation, in-depth observation, and triangulation. The results showed that the tutor teachers' perceptions of PPL-2 teacher skills in the learning delivery process were quite good but still had shortcomings that need improvement for future instructions. Keywords: Basic Teaching Skills, Perceptions of Tutor Teacher, Teaching Practice Program.